2015
DOI: 10.1016/j.celrep.2015.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated SF3B1 Hotspot Mutations Induce Cryptic 3′ Splice Site Selection through Use of a Different Branch Point

Abstract: Recurrent mutations in the spliceosome are observed in several human cancers, but their functional and therapeutic significance remains elusive. SF3B1, the most frequently mutated component of the spliceosome in cancer, is involved in the recognition of the branch point sequence (BPS) during selection of the 3' splice site (ss) in RNA splicing. Here, we report that common and tumor-specific splicing aberrations are induced by SF3B1 mutations and establish aberrant 3' ss selection as the most frequent splicing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

49
526
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(600 citation statements)
references
References 48 publications
49
526
4
2
Order By: Relevance
“…(D) Intron mutations that reduce pairing with U2 snRNA (U257C and A258C) are sensitive to hsh155 mutations analogous to those found in human disease, whereas the 5 ′ SS, 3 ′ SS, and branch nucleophile mutations are not. Darman et al 2015;DeBoever et al 2015;Alsafadi et al 2016), similar to prp5 mutants in yeast (Xu and Query 2007).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…(D) Intron mutations that reduce pairing with U2 snRNA (U257C and A258C) are sensitive to hsh155 mutations analogous to those found in human disease, whereas the 5 ′ SS, 3 ′ SS, and branch nucleophile mutations are not. Darman et al 2015;DeBoever et al 2015;Alsafadi et al 2016), similar to prp5 mutants in yeast (Xu and Query 2007).…”
mentioning
confidence: 82%
“…Disease-related mutations cluster in proteins involved in spliceosome assembly, particularly ones important for intron recognition, such as SF3B1 (also known as SAP155, SF3b155, and Hsh155p), SRSF1, and U2AF (Yoshida et al 2011;Quesada et al 2012). In disease-related SF3B1 mutants, changes in branch site (BS) usage have been identified (Darman et al 2015;Alsafadi et al 2016;Kesarwani et al 2016); however, the mechanisms by which these mutations affect splicing are largely unknown.…”
mentioning
confidence: 99%
“…Interestingly, since submission of our work, Darman et al reported findings fully confirming our results. They also showed the consequences of SF3B1 mutations on transcription through the generation of nonsense-mediated mRNA decay-sensitive aberrant spliced transcripts 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Most mutations are missense mutations localized within the HEAT domain repeats lying in the carboxyterminal moiety of the protein, indicating a gain of function. Indeed, SF3B1 mutations in various cellular contexts are associated with abnormal splice events [51], which result from promotion of alternative branchpoint usage [52][53][54] (Fig. 2).…”
Section: Mutations Of the Sf3b1 Gene And Rna Biologymentioning
confidence: 99%